(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the comparison of tempeh fermentation efficiency between traditional methods and modern methods based on fermentation parameter control. The research method used was a systematic literature review of 23 accredited national journal articles indexed by SINTA and published between 2013 and 2024. Articles were selected based on inclusion criteria covering discussions on fermentation parameters, tempeh product quality, and fermentation method comparisons. Data were analysed descriptively and comparatively by examining aspects of fermentation time, quality consistency, product yield, and microbial contamination levels. The results of the study show that modern fermentation methods that apply temperature control and the use of standardised starters can shorten fermentation time by 18–24% compared to traditional methods. In addition, modern methods produce better quality consistency, as indicated by lower protein content and texture variation. Product yield also increased by 12–15%, accompanied by lower levels of pathogenic microbial contamination. These findings indicate that the application of modern fermentation methods has the potential to improve the efficiency and quality of tempeh production and can be a relevant alternative for the development of small and medium-scale tempeh industries without eliminating local food characteristics.